Assessing the impact of inventory management practices on production performance in the beverage production industry. The moderating role of dynamic capabilities. - Aidoo Kwesi Baafo (KNUST, 2024)
A thesis submitted to the department of supply chain and information systems, school of business in partial fulfillment of the requirements for the award of the degree of master of science logistics & supply chain management